2019
DOI: 10.17509/ijal.v9i2.20218
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of 4Cs-based reading to foster 21st-century learning competencies

Abstract: The omnipresence of 4Cs at tertiary education has shifted the attention of language classroom teachings toward the mastery of multifaceted intelligences. Resultant teaching praxis subsequently calls forth students’ high literacy, which affects the nature and extent of success and failure. This study strived to scrutinize how the 4Cs approach in Reading courses scaffolds students’ multidimensional 21st-century learning competencies. Data were collected through online survey and focus group discussion, with dedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Some studies have investigated the application of the 21st century skills in language teaching (Suto and Eccles, 2014;Bedir, 2019;Imamyartha et al, 2019;Azhary and Ratmanida, 2021). Azhary and Ratmanida (2021) showed that 21st century skills should be well assimilated in lesson plans that are not controlled, but are made creatively with learning activities that are aligned with the acquisition of the 4Cs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies have investigated the application of the 21st century skills in language teaching (Suto and Eccles, 2014;Bedir, 2019;Imamyartha et al, 2019;Azhary and Ratmanida, 2021). Azhary and Ratmanida (2021) showed that 21st century skills should be well assimilated in lesson plans that are not controlled, but are made creatively with learning activities that are aligned with the acquisition of the 4Cs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teachers are expected to be immersed and have acquired technological knowledge and instructional information for 21st century learners. The findings of Imamyartha et al (2019) on research in higher education revealed that 4Cs can be integrated in reading instruction. The assumed integration could aid instructors to innovatively 10.3389/feduc.2022.998987 construct learning conducive to a 21st century setting that supports the metacognition of learners, and acquisition of sufficient level of knowledge.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations